MENUJU ERA GLOBALISASI PENDIDIKAN: Tantangan dan Harapan bagi Perguruan Tinggi di Tanah Air - Wayong, Mohammad (Inspiratif Pendidikan, 2017)
The global insight is a perspective arising from the awareness that in this life everything is always related to the wider world, the global world. Every college in the homeland is no longer possible to isolate themselves from global influence. Universities in the country have been part of the world movement, so that each institution needs to pay attention to the interests of fellow institutions. Every practice in college needs to avoid narrow mindedness, compartmentalized by subjective, primordial and thinking with a pragmatic approach.